2013
DOI: 10.1136/bmjqs-2013-002089
|View full text |Cite
|
Sign up to set email alerts
|

From physician intent to the pharmacy label: prevalence and description of discrepancies from a cross-sectional evaluation of electronic prescriptions

Abstract: Discrepancy rates between the prescriber's note and the e-prescription were similar to the discrepancy rates between the e-prescription and pharmacy label. To reduce outpatient medication errors, a better understanding is needed of the sources of discrepancies that occur within the prescriber's clinic, and those that occur between the clinic and pharmacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Both systems prevented more errors than they generated. It was determined that system‐related errors are frequent but few are detected, and contrary to Cochran et al's () recommendation, systems with fewer drop‐down menus to reduce error risk was recommended.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…Both systems prevented more errors than they generated. It was determined that system‐related errors are frequent but few are detected, and contrary to Cochran et al's () recommendation, systems with fewer drop‐down menus to reduce error risk was recommended.…”
Section: Methodsmentioning
confidence: 94%
“…The literature chosen (Table S1) included three literature reviews (Lapane, Quilliam, & Dore, ; Manchikanti, Whitfield, & Pallone, ; Odukoya & Chui, ), three systematic reviews (Clyne, Bradley, Hughes, Fahey, & Lapane, ; Gagnon, Nsangou, Payne‐Gagnon, Grenier, & Sicotte, ; Motulsky, Lamothe, & Sicotte, ), one review of federal regulation (Schneider & Schneider, ), four descriptive analyses (Gabriel et al., ; Hincapie et al., ; Joseph, Sow, Furukawa, Posnak, & Daniel, ; Westbrook et al., ), three surveys (Amirfar et al., ; Jariwala et al., ; Thomas et al., ), four qualitative interview studies (Abramson et al., ; Bergeron et al., ; Bramble et al., ; Grossman, Cross, Boukas, & Cohen, ), one cross‐sectional study (Cochran et al., ), one time‐motion study (Hollingworth et al., ), and two expert commentaries (Figge, Fox, & Tribble, ; Odukoya & Chui, ). Table S1 provides full details regarding the literature, including author, purpose, methods, results, and conclusions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] Cochran et al found a 2.5 % discrepancy rate between clinic eprescriptions and pharmacy labels. 14 Nanji and colleagues characterized the unrealized potential and residual consequences of e-prescribing. 15 Limitations in communication were described, highlighting the unidirectional (prescriber to pharmacy) flow of electronic information.…”
Section: Discussionmentioning
confidence: 99%
“…They found the combined error rate of these 3 sources to be 2.2%. 30 In England, Abdel-Qader et al found that 8.4% of e-prescriptions dispensed at the time of discharge from the hospital necessitated pharmacist intervention. 31 Kaushal et al and Ammenworth et al both…”
Section: Comparison Of the Benefits And Shortcomings Of Each Prescripmentioning
confidence: 99%